Cutaneous mastocytosis treatment: strategies, limitations and perspectives - Czarny, Justyna; Lange, Magdalena; Ługowska-Umer, Hanna; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Mastocytosis is a rare myeloproliferative disease, characterized by excessive proliferation and accumulation of mast cells in the tissues. In cutaneous mastocytosis (CM), mast cells infiltration is limited to the skin, whereas in systemic mastocytosis (SM) internal organs are involved. The first-line treatment in CM is antimediator therapy (mainly H1 and H2 antihistamines) and short-term topical corticosteroids. Phototherapy is the second-line therapy which may be considered when antihistamines do not produce the expected improvement. New therapeutic options include omalizumab and KIT-targeting agents. Although the disappearance of skin lesions has been reported as a result of cytoreductive therapies in SM, the use of potentially toxic drugs in CM is not recommended. In all adults with mastocytosis and in pediatric patients with severe CM, a persistently elevated serum tryptase level and anaphylaxis in medical history, equipping with epinephrine autoinjector for use in case of anaphylaxis is recommended.